2019
DOI: 10.1007/s11420-019-09720-z
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Coracoid Bone Block Transfer for Shoulder Instability: A Systematic Review

Abstract: Background: Shoulder dislocations can be devastating for an athlete. Coracoid bone block transfer is often used for the treatment of recurrent shoulder instability. Questions/ Purposes: The primary purpose of this study was to determine the rate and mean time of return to sport in athletes after a coracoid bone block transfer at the pre-operative level of competition, a lower level, or a different level. We also sought to determine how return to sport rates after a coracoid bone block procedure compared with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Rossi et al [33] reported that time for RTP after the Latarjet procedure was 3.7 months for patients who performed non-contact/non-overhead sports, compared to 5.1 months for those that performed high-impact/contact [14] found that at 6 months followup, 55% of patients failed to meet criteria for RTP, defined as < 20° loss of ROM as compared with baseline values in any plane, and/or lower strength grade than the baseline value. Several systematic reviews report return to play (RTP) within 5.8 months following the Latarjet procedure [21,28], but the type of sport and preoperative patient characteristics that influence RTP remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Rossi et al [33] reported that time for RTP after the Latarjet procedure was 3.7 months for patients who performed non-contact/non-overhead sports, compared to 5.1 months for those that performed high-impact/contact [14] found that at 6 months followup, 55% of patients failed to meet criteria for RTP, defined as < 20° loss of ROM as compared with baseline values in any plane, and/or lower strength grade than the baseline value. Several systematic reviews report return to play (RTP) within 5.8 months following the Latarjet procedure [21,28], but the type of sport and preoperative patient characteristics that influence RTP remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of the Latarjet procedure have been well documented, with its important role in providing GHJ stability in patients with significant bone loss, failed primary procedures, and in athletes mandating return to elite contact sport. 3,7,10,27,29 In this study, there was no significant difference in the rate of bony union between participants undergoing a Latarjet with unicortical vs. those with bicortical screw fixation. However, the absolute numbers of patients with nonunion were small, and the study was underpowered to demonstrate a statistically significant difference.…”
Section: Discussionmentioning
confidence: 49%
“…20 Indeed, the rate of return to sport is >80%, at 5 months on average, and up to 73% of patients recover before 8 months. 1,21,26 Regarding its effectiveness, some surgeons advocate for Latarjet as the reference technique for all cases of anterior instability, especially in high-risk athletes, even without any bony lesions. 5,11,29 Latarjet is mainly performed as an open surgery.…”
mentioning
confidence: 99%